The Therapy of Vulvar Carcinoma—Evaluation of Surgical Options in a Retrospective Monocentric Study - Peter Jankowski; Sebastian Findeklee; Mihai-Teodor Georgescu; Romina Marina Sima; Meletios P. Nigdelis; Erich-Franz Solomayer; Gilbert Georg Klamminger; Bashar Haj Hamoud (Life, 2023)
(1) Background: Surgical-oncological treatment methods are continuously put to the test in times of evidence-based medicine—notably, a constant reevaluation remains key, especially for tumor entities with increasing incidence such as vulvar carcinoma. (2) Methods: In order to determine the postoperative clinical course of different methods of vulvar excision (vulvectomy, hemivulvectomy) as well as inguinal lymph node removal (lymphadenectomy, sentinel lymph node biopsy) with regard to postoperative wound-healingprocess, perioperative hemorrhage, and re-resection rates, we retrospectively analyzed surgical, morphological and laboratory data of 76 patients with a pathological diagnosed vulvar cancer. (3) Results: Analysis of our data from a single center revealed a comparable perioperative clinical course regardless of the chosen method of vulvar excision and inguinal lymph node removal. (4) Conclusions: Thus, our results emphasize the current multimodality in surgical therapy of vulvar carcinoma, in which consideration of known prognostic factors together with the individual patient’s clinical situation allow guideline-based therapy aimed at maximizing surgical safety.